Late pleistocene and holocene loess deposits of the Southeastern Buenos Aires province, Argentina - Zárate, Marcelo Arístides (1991)
The Late Pleistocene and Holocene loess deposits of the SE Buenos Aires province are composed of four allostratigraphic units that represent four episodes of loess deposition. The first and the second episodes occurred in Late Pleistocene times. The second episode was followed by a soil forming interval (Early Holocene to Mid-Holocene times). The third episode took place at about 5000 yr BP, after the Holocene sea-level maximum when marine regression began. The fourth episode constitutes a historical event of only local significance. Loess shows a fairly constant granulometric and mineralogical composition. The modal fraction consists of very fine sand and coarse silt (3 to 5 phi). They are classified as sandy silts or silty sands. Three grain-size subpopulations are differentiated: coarse, medium and fine. The medium-size subpopulation, which is the most important, consists of most of the very fine sand and coarse silt. It is thought to be transported by modified saltation and short-term suspension during local dust-storms. The mineralogical composition of loess consists of a volcaniclastic assemblage derived mainly from reworked pyroclastic deposits, primary tephras and volcaniclastic sediments. The source area of these materials was located in the lower Colorado river valley about 400 km SW of the studied area. There was also a direct supply by volcanic ash falls.